SINTESIS DAN KARAKTERISASI NANOSELULOSA SERBUK DARI TANDAN KOSONG KELAPA SAWIT MENGGUNAKAN ULTRASONIFIKASI - Tri Yuni Hendrawati; Efrizon Umar; Anwar Ilmar Ramadhan; Alvika Meta Sari; Mutiara Salsabila; Rahmawati Suryani; Firmansyah Firmansyah; Istianto Budhi Rahardja (Jurnal Teknologi, 2023)
Indonesia is the largest palm oil producing country in the world. In the palm oil production process, solid waste is produced, one of which is empty palm fruit bunches (EFB) of 25-26% w/w of the total palm oil raw material. OPEFB has several constituent components such as lignin, hemicellulose and cellulose. The high content of α-cellulose in OPEFB can be used as a base material for making nanocellulose. Nanocellulose was made in this study through delignification, ultrasonication and hydrothermal processes with the aim of obtaining the optimum ultrasonication temperature of nanocellulose. Temperature variations were carried out at 40, 50, 60 and 70 °C for 30 minutes. The results of the synthesis process can be seen visually for each temperature variation. Characterization analysis was performed using SEM (Scanning Electron Microscopy). The correlation between temperature variations (x) to the yield percentage of nanocellulose (y) follows the equation y = 7.921x + 7.345 and R2 = 0.9471. The optimum temperature of the ultrasonication process is 70 °C with a yield of 36.9%. The size of nanocellulose powder is 174.85-460.84 nm with SEM at 70 °C.